Iowa Gambling Task (IGT): twenty years after – gambling disorder and IGT - Brevers, Damien; Bechara, Antoine; Cleeremans, Axel; Noel, Xavier (Frontiers in Psychology, 2013)
The Iowa Gambling Task (IGT) involves probabilistic learning via monetary rewards and punishments, where advantageous task performance requires subjects to forego potential large immediate rewards for small longer-term rewards to avoid larger losses. Pathological gamblers perform worse on the IGT compared to controls, relating to their persistent preference toward high, immediate and uncertain rewards despite experiencing larger losses. In this contribution, we review studies that investigated processes associated with poor IGT performance in pathological gamblers. Findings from these studies seem to fit with recent neurocognitive models of addiction, which argue that the diminished ability of addicted individuals to ponder short-term against long-term consequences of a choice may be the product of an hyperactive automatic attentional and memory system for signaling the presence of addiction-related cues (e.g., high uncertain rewards associated with disadvantageous decks selection during the IGT) and for attributing to such cues pleasure and excitement. This incentive-salience associated with gambling-related choice in pathological gamblers may be so high that it could literally “hijack” resources (“hot” executive functions) involved in emotional self-regulation and necessary to allow the enactment of further elaborate decontextualized problem-solving abilities (“cool” executive functions). A framework for future research is also proposed, which highlights the need for studies examining how these processes contribute specifically to the aberrant choice profile displayed by pathological gamblers on the IGT.